Talent development environment and achievement goal adoption among Korean and Singaporean athletes: Does perceived competence matter? - Wang, C. K. J.; Pyun, D. Y.; Li, C.; Lee, M. S. (International Journal of Sports Science & Coaching, 2016)
The objectives of this study were twofold. The first was to compare differences in perceptions of the talent development environment, achievement goals, and perceived competence, in terms of an individual characteristic (i.e. gender), a cultural characteristic (i.e. country), and their interactions (i.e. gender by country). The second was to examine the moderating effects of perceived competence on the relationships between the talent development environment and achievement goals. Data were collected from 363 athletes in Singapore and 349 athletes in Korea. A series of MANOVAs and path analyses were employed for testing of the main hypotheses. First, in terms of the talent development environment, male athletes scored higher in long-term development focus, communication, support network, and long-term development fundamentals. Second, in terms of achievement goals and perceived competence, male athletes scored higher in competence and performance-approach goal, but female athletes scored higher in mastery-avoidance goal. While Singaporean athletes scored higher in perceived competence, mastery-approach, and mastery-avoidance, Korean athletes scored higher in performance-avoidance. Lastly, the path analysis provided empirical evidence supporting the moderation effects of perceived competence on the relationships between the talent development environment and achievement goal adoption. ABSTRACT FROM AUTHOR